The Effect of Tax Knowledge and Tax Sanctions on Taxpayer Compliance in The Millennial Generation in Karawang with Tax Awareness as Moderation Variable - Karo, Rospita Br; Herawati, Vinola (Manunggal Halim Jaya, 2024)
This study aims to determine the effect of tax knowledge and tax sanctions on taxpayer compliance in the millennial generation in Karawang, with tax awareness as a moderating variable. This study's sample is the Millennial Generation in Karawang, Generation Y, born between 1982 and 1996. Disseminating questionnaires online, namely filling out Google forms with as many as 110 samples. Hypothesis testing is using a structural equation model. The results of this study provide the following: It can be concluded that tax knowledge positively influences taxpayer compliance, and tax sanctions do not. Furthermore, tax awareness can strengthen the positive perspective of tax knowledge on taxpayer compliance. Tax awareness can strengthen the negative perspective of tax sanctions on taxpayer compliance.